Basic Mathematics and TOEFL Training for Academic and Interview Preparation in Society 5.0 Era - Sinta S; Maya Saftari; Yuni Iswanto (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the era of society 5.0, the role of lecturers/teachers is indispensable in creating superior human resources in achievement and religious in worship so that all can go hand in hand and be in line with human aspirations to live in benefit. Basic mathematics training which is a venue for testing academic potential in entering higher education as well as TOEFL English which has become part of students' lives. From this activity, we know that this training is very useful for all students at the third level at senior high school.